Polarizing Patriots: Divergent Responses to Patriotic Imagery in News Coverage of Terrorism. (January 2013) - Gelpi, Christopher; Roselle, Laura; Barnett, Brooke
We demonstrate that the use of patriotic imagery in news reporting may increase rather than decrease public polarization regarding foreign policy issues. Specifically, we examine the impact of patriotic imagery in the context of an online news story about terrorism on individuals' attitudes toward civil liberties in the "war on terror" and spillover effects on support for the war in Afghanistan. We expect that images of the American flag will be associated with differing clusters of values depending on the level of right-wing authoritarianism (RWA) that an individual's personality exhibits. Specifically, we expect that flag imagery will decrease support for civil liberties and increase support for the war in Afghanistan among individuals who are high in RWA. But we expect flag exposure to have the opposite effect among those who are low in RWA. Finally, we expect patriotic imagery cues will influence only individuals who are not a part of the terrorism "issue public." We test these hypotheses with an experiment that presents participants with a single news story on the Times Square bomber. The experiment frames the news story as coming from Fox News, CNN, or MSNBC and varies the presence or absence of patriotic flag imagery in the pictures accompanying the news story. The results provide strong support for our expectations regarding the contingent impact of patriotic imagery as well as our expectations regarding the spillover effects of news coverage on terrorism on attitudes toward Afghanistan.